Engineering properties of rocks - Zhang, Lianyang (Elsevier, 2017)
"More often than not, it is difficult or even impossible to obtain directly the specific rock parameters of interest using the situ methods. The procedures for measuring most rock properties are also time consuming and expensive. As an alternative, the typical values and/or empirical correlations of similar rocks are commonly used to estimate the specific parameters needed. However, these values and correlations come in many forms and are scattered across the different sources. It is often difficult, time consuming, or even impossible for a practitioner to find appropriate information in order to determine the required rock parameters. Based on the author's extensive experience, Engineering properties of rocks offers a single source of information and serves as a valuable tool for practitioners to evaluate the properties of rocks. It systematically describes the classification and characterization of intact rock, rock discontinuities and rock masses, and presents the various indirect methods for estimating the deformability, strength, and permeability of these components as well as the situ rock stresses"--Back cover.